'Being defined': large-bodied women's experiences as healthcare consumers. Issue 1 (2nd January 2018) - Williams, Danielle
ABSTRACT: Despite an increasingly pathologised discourse on overweight and obesity, the clinical experiences of large bodied individuals remain relatively unexplored. In addition, interventions targeting overweight and obesity have generally failed to recognise the role that weight related discrimination and stigma play in both the uptake of interventions and the experience of healthcare consumers. This Australian research used a grounded theory approach, informed by constructivism, to further understanding and generate dialogue about the experiences of large bodied female healthcare consumers. Participants included 22 women, who were purposively sampled, all of whom identified as overweight or obese. Data was collected from two major sources: intensive interviews with participants and literature. For the participants in this study, being overweight or obese created a significant barrier to positive clinical interactions with their medical professionals. Women described their interactions with medical professionals, particularly general practitioners (GPs) as the most challenging to manage. Participants believed that when they became patients, they were defined by their body size, which worked to create a one-dimensional identity – that of a fat patient. These findings suggest that weight-related discrimination and stigma has a significant impact on both the clinical interaction, and the health and wellbeing of large bodied, female healthcare consumers.